2013
DOI: 10.1111/padm.12043
|View full text |Cite
|
Sign up to set email alerts
|

Looking at a Job's Social Impact Through Psm‐tinted Lenses: Probing the Motivation–perception Relationship

Abstract: We explore here the relationship between employees' public service motives and the way they perceive the social impact of their work. Our purpose is twofold. First, while past researchers have examined part of this relationship, largely from the opposite causal direction, we seek to supplement the field's current understanding of the organizational consequences of public service motivation (PSM), especially its potential impact on an employee's perceived social impact. Together with a cross‐sectional study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 46 publications
(68 reference statements)
0
38
0
Order By: Relevance
“…In a quasi-experiment with fundraisers serving a public university, Grant (2008 ) showed that employees ' motivation could be increased by connecting them to the prosocial impact of their work. Moreover, Stritch and Christensen (2014 ) found that PSM strongly predicted employees ' perceptions of the social impact of their jobs.…”
Section: Public Service Motivation and Psychological Empowermentmentioning
confidence: 98%
“…In a quasi-experiment with fundraisers serving a public university, Grant (2008 ) showed that employees ' motivation could be increased by connecting them to the prosocial impact of their work. Moreover, Stritch and Christensen (2014 ) found that PSM strongly predicted employees ' perceptions of the social impact of their jobs.…”
Section: Public Service Motivation and Psychological Empowermentmentioning
confidence: 98%
“…We hypothesize differences among sectors in employees’ perceptions of the social impact of their work. Individuals with strong public‐service‐oriented motives might be more likely to emphasize the prosocial aspects of their work (Stritch and Christensen ). In addition, public organizations provide public goods and services to a community, whereas private sector employees are more likely to be involved in market‐driven exchanges of goods and services with individual customers.…”
Section: Perception Of Social Impactmentioning
confidence: 99%
“…We hypothesize diff erences among sectors in employees' perceptions of the social impact of their work. Individuals with strong public-service-oriented motives might be more likely to emphasize the prosocial aspects of their work (Stritch and Christensen 2014).…”
Section: Perception Of Social Impactmentioning
confidence: 99%
“…It is somewhat related to intrinsic motivation, in the sense that there is no direct (future pecuniary) reward needed for motivation, even though the locus of control remains outside the self (Deci and Ryan ; Vandenabeele ). Individuals with high levels of PSM also tend to be more perceptive of the societal impact of their work (Stritch and Christensen ).…”
Section: Data and Measurementmentioning
confidence: 99%
“…It is somewhat related to intrinsic motivation, in the sense that there is no direct (future pecuniary) reward needed for motivation, even though the locus of control remains outside the self (Deci and Ryan 1985;Vandenabeele 2007). Individuals with high levels of PSM also tend to be more perceptive of the societal impact of their work (Stritch and Christensen 2014). PSM consists of three dimensions: attraction to public policy making, commitment to the public interest, and compassion (Perry 1996;Vandenabeele and Van de Walle 2008).…”
Section: Control Variablesmentioning
confidence: 99%